Avaliação da atividade pró e anti-inflamatória das células do colostro humano estimuladas pelo óleo de soja - Silva, Katleyn Polizeli Galvão (2021)
Efficient breastfeeding can generate several benefits to newborns, nutrition, immune system formation, protection against different types of pathologies and even better cognitive development. The study of products of natural origin that can enhance the cells of the immune system and give the newborn greater protection has been highlighted. The aim of this study is to evaluate the pro- and anti-inflammatory activity of human colostrum cells in the presence of two categories of soybean oil: crude (SOC) and refined (SOR). Twenty-four samples were collected from healthy mothers aged between 18 and 40 years. For all analyzes in this study, the samples were divided into 3 groups: 1- colostrum; 2 – colostrum + OSB and 3 – colostrum + OSR. Mononuclear cells (MN) from colostrum were also obtained using the Ficoll-paque density separation method. Cell viability was determined by fluorescence method. The determination of superoxide anion release was performed using the Cytochrome C reduction method. The cytokines IL-12 and IL-10 were quantified by the Cytometric Bead Array kit. In the rheological analysis, both OSB and OSR oils showed non-linear behavior and were classified as non-newtonian fluids. When colostrum was placed with the OSB and OSR, the rheological characteristics such as shear rate and viscosity remained similar to the control group (the rheological analysis of colostrum only). The viability of colostrum MN cells with OSB and OSR was greater than 90%. In superoxide anion quantification, the MN + OSB cell group presented the highest superoxide anion release (17.30 ± 4.75) when compared to the control (5.54 ± 1.14). The concentrations of IL12 and IL-10 cytokines in colostrum were not modified in the presence of any of the oils, however the IL-12 cytokine showed a slight tendency to increase when compared to the control. It was also observed that there is a strong correlation between the IL-12 cytokine and the viscosity of the groups stimulated by the OSB, and a weak correlation between the same variables in the group stimulated by the OSR. Another weak correlation was also noted in relation to superoxide anion release and IL-12 cytokine in the OSB-stimulated group. With the data obtained in this study, it is possible to suggest that OSB had better immunomodulatory characteristics than OSR, this opens up other paths for a better observation of its effects.